2020
DOI: 10.1210/clinem/dgz301
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Autoimmune Syndrome: A Case of Clopidogrel-induced Autoimmune Hypoglycemia

Abstract: Context Insulin autoimmune syndrome (IAS) is characterized by hyperinsulinemic hypoglycemia with elevated anti-insulin antibodies. Most commonly observed in the Japanese population, elsewhere it is rare and associated with autoimmune diseases, plasma cell dyscrasias, or sulfhydryl group medications. The active metabolite of clopidogrel has a sulfhydryl group and here we report a case of clopidogrel-induced IAS. Case Description … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…The top three drugs were methimazole, alipoic acid, and tiopronin (24). Clopidogrel was the fifth most common drug if adding our case (5,17,18,(24)(25)(26). Moreover, 11 of the 134 AIH cases with unknown causes were considered to have been caused by clopidogrel tablets, as each of these patients had a history of exposure to clopidogrel or a history of coronary heart disease or coronary or carotid artery stent implantation (19,(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The top three drugs were methimazole, alipoic acid, and tiopronin (24). Clopidogrel was the fifth most common drug if adding our case (5,17,18,(24)(25)(26). Moreover, 11 of the 134 AIH cases with unknown causes were considered to have been caused by clopidogrel tablets, as each of these patients had a history of exposure to clopidogrel or a history of coronary heart disease or coronary or carotid artery stent implantation (19,(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 81%
“…Methylprednisone and dexamethasone can also be used (17). In the case of refractory hypoglycemia, plasmapheresis may rapidly reduce the IAA titer (18), and it has also been successfully treated with rituximab to deplete B lymphocytes (19).…”
Section: Discussionmentioning
confidence: 99%
“…There have been few case reports of IAS during clopidogrel therapy. [5][6][7][8] The proposed explanation for hypoglycemia is that the clopidogrel sulfhydryl group interacts with the insulin molecule's disulfide bond, rendering it immunogenic. Consequently, insulin autoimmune antibodies (IAAs) produced circulate in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Te most common such drugs are methimazole [16,17] and lipoic acid [18][19][20][21][22]. Others include clopidogrel [23][24][25][26], proton pump inhibitors [27] (pantoprazole [8], omeprazole), carbimazole [28], coenzyme Q10 [29], antituberculosis drugs [30], gliclazide [31], captopril [32], loxoprofen sodium [33], and albumin preparations [34], within the preceding week. Studies have shown that approximately half of IAS patients have a history of medication before the onset of the disease, and more than 90% of them used drugs containing sulfhydryl groups such as α-lipoic acid or its metabolites [35].…”
Section: Classifcation Of Iasmentioning
confidence: 99%